Assessment of distant-site rescue elements for CRISPR toxin-antidote gene drives - Chen, Jingheng; Xu, Xuejiao; Champer, Jackson (Frontiers in Bioengineering and Biotechnology, 2023)
Gene drive is a genetic engineering technology that can enable super-mendelian inheritance of specific alleles, allowing them to spread through a population. New gene drive types have increased flexibility, offering options for confined modification or suppression of target populations. Among the most promising are CRISPR toxin-antidote gene drives, which disrupt essential wild-type genes by targeting them with Cas9/gRNA. This results in their removal, increasing the frequency of the drive. All these drives rely on having an effective rescue element, which consists of a recoded version of the target gene. This rescue element can be at the same site as the target gene, maximizing the chance of efficient rescue, or at a distant site, which allows useful options such as easily disrupting another essential gene or increasing confinement. Previously, we developed a homing rescue drive targeting a haplolethal gene and a toxin-antidote drive targeting a haplosufficient gene. These successful drives had functional rescue elements but suboptimal drive efficiency. Here, we attempted to construct toxin-antidote drives targeting these genes with a distant-site configuration from three loci in Drosophila melanogaster. We found that additional gRNAs increased cut rates to nearly 100%. However, all distant-site rescue elements failed for both target genes. Furthermore, one rescue element with a minimally recoded sequence was used as a template for homology-directed repair for the target gene on a different chromosomal arm, resulting in the formation of functional resistance alleles. Together, these results can inform the design of future CRISPR-based toxin-antidote gene drives.